2012
DOI: 10.1111/pce.12006
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast ultrastructure regeneration with protection of photosystem II is responsible for the functional ‘stay‐green’ trait in wheat

Abstract: CN17 is a functional stay-green wheat variety that exhibits delayed leaf senescence and enhanced photosynthetic competence. To better understand these valuable traits, levels of chlorophyll a and b, soluble proteins, unsaturated fatty acids, and other components of CN17 were assayed. In addition, chloroplast ultrastructure, chloroplast number, and differences in gene expression between CN17 and a control variety, MY11, were examined. By 21 d postanthesis (DPA), CN17 leaves exhibited a significantly higher maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 52 publications
(81 reference statements)
0
31
0
Order By: Relevance
“…In crop plants species, stay-green enables a plant to maintain greenness and continue photosynthesising even under stress (Borrell et al 2014). Staygreen is associated with antioxidant status and photosystem II of the mesophyll cells (De Simone et al 2014;Luo et al 2013b). In many cereal crops, staygreen plants generally have higher chlorophyll contents and are more tolerant to abiotic stresses during grain filling.…”
Section: Introductionmentioning
confidence: 99%
“…In crop plants species, stay-green enables a plant to maintain greenness and continue photosynthesising even under stress (Borrell et al 2014). Staygreen is associated with antioxidant status and photosystem II of the mesophyll cells (De Simone et al 2014;Luo et al 2013b). In many cereal crops, staygreen plants generally have higher chlorophyll contents and are more tolerant to abiotic stresses during grain filling.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, 32 expression sequence tags (ESTs) were identified in CN17 during the delayed leaf senescence stage; these tags, which were up-regulated in stay-green CN17, and showed high homology with known or annotated genes that are associated with senescence-related processes in wheat, rice, barley, pea, and Arabidopsis. Among these ESTs, 31.3% were directly related to photosynthesis and leaf senescence processes, whereas the other ESTs were indirectly related to these processes (Luo et al 2013). However, the greatest shortage of this study is the unknown chromosomal locations of the ESTs.…”
Section: Introductionmentioning
confidence: 88%
“…During senescence, leaf cells experience dramatic changes in the expression of genes that are involved in photosynthesis, hydrolase activity, oxidoreduction, cellular processes, photorespiration, lipid transport, and biosynthesis pathways (Buchanan-Wollaston et al 2005;Luo et al 2013); because of the genetic variations, significant differences in the rate and degree of leaf senescence are observed during the important growth stages (e.g., the grain-filling period) both among species and within species (Thomas and Howarth 2000). Previous studies have reported stay-green phenotypes that result from delayed leaf senescence in many species, which includes several crop species such as wheat (Hortensteiner 2009;Luo et al 2013). Staygreen cultivars are divided into two principal categories: functional stay-green with photosynthetic activity and cosmetic stay-green without photosynthetic activity (Hortensteiner 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations